2017
DOI: 10.1002/2016gc006640
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of the Sr/Ca proxy in recording ocean temperature in the western Atlantic coral Siderastrea siderea

Abstract: Massive corals provide a useful archive of environmental variability, but careful testing of geochemical proxies in corals is necessary to validate the relationship between each proxy and environmental parameter throughout the full range of conditions experienced by the recording organisms. Here we use samples from a coral-growth study to test the hypothesis that Sr/Ca in the coral Siderastrea siderea accurately records sea-surface temperature (SST) in the subtropics (Florida, USA) along 350 km of reef tract. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Smith et al () did find a small yet statistically significant relationship between O. faveolata SST residuals and both calcification and extension parameters on an interannual basis; however, they concluded that the potential influence of either calcification rate or linear extension rate explained <10% of the residual SST values, and that on a monthly basis, the relationship was trivial. Kuffner, Roberts, et al () also found a significant relationship between Sr/Ca and linear extension in the coral species, S. siderea , but it was not linear; Sr/Ca showed a cold bias when growth rates dropped below a linear extension threshold of 1.7 mm/year.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Smith et al () did find a small yet statistically significant relationship between O. faveolata SST residuals and both calcification and extension parameters on an interannual basis; however, they concluded that the potential influence of either calcification rate or linear extension rate explained <10% of the residual SST values, and that on a monthly basis, the relationship was trivial. Kuffner, Roberts, et al () also found a significant relationship between Sr/Ca and linear extension in the coral species, S. siderea , but it was not linear; Sr/Ca showed a cold bias when growth rates dropped below a linear extension threshold of 1.7 mm/year.…”
Section: Resultsmentioning
confidence: 93%
“…We note that the maximum RMS value in all cases occurred in the summer of 1998 (Figure f), which was a prominent El Niño year. Thermal anomalies associated with El Niño are known to generate coral growth anomalies that may cause especially high variability in coral Sr/Ca (Hetzinger et al, ; Kuffner, Roberts, et al, ). It may, therefore, be best to avoid known temperature stress events in calibration regressions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal extension and/or calcification rates have been invoked to explain, and in some cases correct for (Maier et al, ; Goodkin et al, , 2007) intercolony Sr/Ca and δ 18 O offsets in a variety of coral species (e.g., Alibert & McCulloch, ; Cohen & Hart, ; Gagan et al, ; Goodkin et al, ; Kuffner et al, , ; Lough & Barnes, ; Suzuki et al, ). Coral biomineralization models suggest that corals incorporate less Sr 2+ relative to Ca 2+ when they calcify faster, and vice versa (Gaetani & Cohen, ), consistent with experiments that manipulate inorganic aragonite precipitation rates (Holcomb et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive empirical data underscores the utility of coral Sr/Ca ratios as a robust proxy for ocean temperature (Beck et al, 1992;DeLong et al, 2013;Inoue et al, 2007;Kuffner et al, 2017;Quinn & Sampson, 2002;Sinclair, 2015;Smith et al, 1979;Weber, 1973), even though a complete mechanistic framework for temperature-dependent incorporation of Sr into coral skeletal aragonite remains elusive (Allison et al, 2011;Gaetani & Cohen, 2006;Gagnon et al, 2012;Sinclair et al, 2006). Paired measurements of coral Sr/Ca and coral δ 18 O allow for the quantification of both SST and δ 18 O sw variations in the past (e.g., Ren et al, 2002;Cahyarini et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%